1964
DOI: 10.1002/bip.1964.360020307
|View full text |Cite
|
Sign up to set email alerts
|

The exclusion of large solutes by cartilage proteinpolysaccharide

Abstract: synopsisThe dialysis technique of Ogston and Phelps, using a Millipore filter as a membrane to measure the effect of a nondialyiable macromolecule on the distribution of dialyzable macromolecules, has been used to measure the effect of a compound of protein and polysaccharide (PP-L), isolated from cartilage, on the distribution of some dialyzable macromolecules. PP-L (1%) in buffer acts as if part of its solution volume were unavailable as follows: 55% for serum albumin, 64% for chondroitin sulfate made by alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1965
1965
1985
1985

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 20 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…The virtual exclusion of serum proteins from such cartilages was postulated by Gerber and Schubert (21); thus the nature and function of this new pool of interstitial proteins is being investigated. ADDENDUM Additional support to the conclusion reached in this paper was found in analyses of well-characterized proteinpolysaccharides provided us recently by Dr. Lawrence Rosenberg.…”
Section: Discussionmentioning
confidence: 99%
“…The virtual exclusion of serum proteins from such cartilages was postulated by Gerber and Schubert (21); thus the nature and function of this new pool of interstitial proteins is being investigated. ADDENDUM Additional support to the conclusion reached in this paper was found in analyses of well-characterized proteinpolysaccharides provided us recently by Dr. Lawrence Rosenberg.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been made into the diffusive permeability of certain connective tissues such as intervertebral disc (Paulson et al, 1951), articular cartilage (Kantor & Schubert, 1957;Brower et al, 1962;Gerber & Schubert, 1964;Maroudas, 1970;Lotke & Granda, 1972) and cornea (Hedbys, 1963). The difficulties that present themselves in studying Vol.…”
mentioning
confidence: 99%
“…Application of milder methods, such as physical disintegration of the tissue by high speed homogenisation, yields the acid glycosaminoglycans linked firmly to protein moieties by covalent bonds (see for example Shatton and Schubert, 1954;Gerber, Franklin and Schubert, 1960). Erroneous implications should not be drawn from the persistent use of the generic nomenclature of polysaccharide-protein complexes for these materials when obviously the term compound would be far more appropriate.…”
Section: The Complexesmentioning
confidence: 99%
“…However, it has been shown that bovine nasal septum cartilage yields two varieties of chondroitin sulphate-protein complex, distinguished by their differential sedimen-tation in the ultracentrifuge (Gerber, Franklin and Schubert, 1960). The large particle fraction (designated PP-H) has a substantially higher protein content than the lighter (socalled PP-L) fraction.…”
Section: The Complexesmentioning
confidence: 99%
See 1 more Smart Citation